Effects of Vernonia amygdalina Leaf on Nutritional and Biochemical Parameters in Alloxan-Induced Diabetic Rats - Amaechi, Nuria Chinonyerem; Ojimelukwe, Philippa Chinyere; Onoja, Samuel Okwudili (Journal of Nutritional Therapeutics, 2018)
The effects of Vernonia amygdalina leaf on the nutritional and biochemical parameters in alloxan-induced diabetic rat were investigated. Vernonia amygdalina (VA) leaf was squeeze-washed, dried, pulverized and mixed with standard feed at 2.5%, 5%, 10% and 20%. The proximate nutrient composition of the standard and prepared rations was determined. The Vernonia amygdalina incorporated rations and standard ration were fed to alloxan-induced diabetic rats for 70 consecutive days. Thereafter the nutritional and biochemical parameters as well as the histopathology of pancreas vital organs of the treated rats were determined. The Vernonia Amygdalina at 2.5% inclusion rate significantly (p < 0.05) reversed the nutritional indices and biochemical parameters which were compromised in diabetic rats fed with standard ration alone. The VA also reversed the degenerative changes in the pancreatic islet induced by alloxan. Vernonia Amygdalina has potent antidiabetic activity and its incorporation in excess of 5% in the diet should be avoided.